Copper‐Catalyzed Domino Reaction Involving Nitro as an Unexpected Leaving Group: Construction of Dibenzo‐Fused Azepinone Ring. Issue 20 (26th September 2016) - Sunke, Rajnikanth; Ramarao, E. V. Venkat Shivaji; Nallapati, Suresh Babu; Medisetti, Raghavender; Kulkarni, Pushkar; Kapavarapu, Ravi Kumar; Bankala, Ramudu; Parsa, Kishore V. L.; Pal, Manojit
Abstract: A copper‐catalyzed new domino reaction allowed the facile and direct construction of the dibenzo‐fused azepinone ring leading to an array of novel small molecules. The co‐catalyst, ligand or additive free one‐pot method afforded a unique class of functionalized derivatives, one of which showed encouraging PDE4 inhibition in vitro and apoptosis in vivo . Abstract :